Mitophagy, Inflammasomes and Their Interaction in Kidney Diseases: A Comprehensive Review of Experimental Studies - Wang Y; Song D; Tang L (Journal of Inflammation Research, 2023)
Yulin Wang, Dongxu Song, Lin Tang Department of Nephrology, Zhengzhou University First Affiliated Hospital, Zhengzhou, Henan, 450052, People’s Republic of ChinaCorrespondence: Lin Tang, Department of Nephrology, Zhengzhou University First Affiliated Hospital, 1 Jianshe Road, Zhengzhou, Henan, 450052, People’s Republic of China, Email tanglin@zzu.edu.cnAbstract: Mitophagy is an important mechanism for mitochondrial quality control by regulating autophagosome-specific phagocytosis, degradation and clearance of damaged mitochondria, and involved in cell damage and diseases. Inflammasomes are important inflammation-related factors newly discovered in recent years, which are involved in cell innate immunity and inflammatory response, and play an important role in kidney diseases. Based on the current studies, we reviewed the progress of mitophagy, inflammasomes and their interaction in kidney diseases.Keywords: mitophagy, inflammasomes, kidney diseases, acute kidney injury, chronic kidney disease, diabetic kidney disease